Weapons of mass distraction: The impact of technology on our children's brains. (2nd October 2022) - Wigley, Robert
Abstract : Children are getting devices at a younger age and spending more time on them. Twenty-nine per cent of babies under the age of one watch TV and video content for about ninety minutes a day, while 64 per cent of children watch a little more than 2 hours of content a day between their first and second birthdays. Forty-two per cent of children under the age of eight have their own tablet.